First record of four Ectoparasites species in Trachurus trachurus in Syrian marine waters - فاضل, منار; محمد حسن; علي نيصافي (Latakia University Journal -Biological Sciences Series, 2024)
The present study aimed at investigating the Ectoparasites of Trachurus trachurus in the Syrian marine waters. A total of 150 individuals were collected during two years from waters of Latakia (RasAlBaseet) from February 2021 to February 2023. The skin, buccal cavity, nostrils and gills of all individuals were examined. We isolated two Ectoparasites species Pseudaxine trachuri and Gastrocotyle trachuri belonging to Monogenea, Family: Gastrocotylidae with a prevalence of 11.33% and 12.66%, and an intensity of 1.41 and 1.36 parasite/fish respectively. Our results showed that the infection of the gills of T. trachurus by these two isolated Ectoparasites species have been observed in all seasons during the study period. We also isolated Lamellodiscus elegans that belongs to the Monogenea, Family: Diplectanidae from T. trachusus gills with a prevalence of 12.66% and an intensity of 1.31 p/f. In addition, we isolated the genus Gnathia sp. (Familly: Gnathidae) in only one individual during the winter. This represents the first records of these Ectoparasites species in Trachurus trachurus in the Syrian marine waters.